Bolometric IR photoresponse based on a 3D micro-nano integrated CNT architecture - Al-Mafrachi, Yasameen; Yadav, Sandeep; Preu, Sascha; Schneider, Jörg J.; Yilmazoglu, Oktay (Beilstein Journal of Nanotechnology, 2024)
A new 3D micro-nano integrated M-shaped carbon nanotube (CNT) architecture was designed and fabricated. It is based on vertically aligned carbon nanotube arrays composed of low-density, mainly double-walled CNTs with simple lateral external contacts to the surroundings. Standard optical lithography techniques were used to locally tailor the width of the vertical block structure. The complete sensor system, based on a broadband blackbody absorber region and a high-resistance thermistor region, can be fabricated in a single chemical vapor deposition process step. The thermistor resistance is mainly determined by the high junction resistances of the adjacent aligned CNTs. This configuration also provides low lateral thermal conductivity and a high temperature coefficient of resistance (TCR). These properties are advantageous for new bolometric sensors with high voltage responsivity and broadband absorption from the infrared (IR) to the terahertz spectrum. Preliminary performance evaluations have shown current and voltage responsivities of 2 mA/W and 30 V/W, respectively, in response to IR (980 nm) absorption for a 20 × 20 μm2 device. The device exhibits an exceptionally fast response time of ≈0.15 ms, coupled with a TCR of −0.91 %/K. These attributes underscore its high operating speed and responsivity, respectively. In particular, the device maintains excellent thermal stability and reliable operation at elevated temperatures in excess of 200 °C, extending its potential utility in challenging environmental conditions. This design allows for further device miniaturization using optical lithography techniques. Its unique properties for mass production through large-scale integration techniques make it important for real-time broadband imaging systems.
Keywords: 3D micro-nano architecture; blackbody absorption; CNT microbolometer; high responsivity; high spatial resolution